Determination of the Efficiencies of the Prokinetics in Ruminants with Postoperative Ileus Using Pro-Inflammatory Markers - Altan, Semih; Dönmez, Kaan; Altan, Feray; Alkan, Fahrettin (Acta Scientiae Veterinariae, 2018)
Background: Recently, the role of inflammation triggered by handling of the intestine various gastrointestinal (GI) surgeries is generally accepted as the key event in postoperative ileus (POI). Because, prokinetics have been increased the smooth muscle contractions and may act by attenuating the inflammatory process in the GI tract, they have been used the treatment of POI in human and animals. There are many in vivo analysis techniques of GI motility. However, there have not yet been studied associated with the evaluation of the inflammatory response. Therefore, it was aimed to evaluate the efficiencies of 3 different prokinetics from inflammatory response during experimentally-induced POI. Materials, Methods & Results: Twenty healthy lambs (30-45 days old) were randomly assigned to four groups. In all groups, enterotomy was performed on the ileum. Erythromycin and metoclopramide were administered to the ERT and MET groups before the surgery, respectively, while lidocaine was administered to the LID group as bolus before and continuous rate infusion during the surgery. Physiological saline was administered to the lambs in control group as placebo before the surgery. Blood samples were collected before surgery (~30-45 min), at the end of surgery (0 h), and at the postoperative 1, 3, 5, 10, 48, 72 and 96 h. The concentrations of serum amyloid A (SAA), haptoglobin (HPT), fibrinogen (FIB) as acute phase proteins (APPs), thiobarbituric acide reactant substrate (TBARs), myeloperoxidase (MPO) as reactive oxygen species, and transforming growth factor-beta (TGF- β) as a cytokine were measured with ELISA reader. In terms of time points, it was found that FIB was statistically higher in ERT group at the 1st h, in MET and LID groups at the 10th h, and in LID group at the 48th and in MET group at the 72 h (P < 0.05). It was found that SAA was higher in MET group at the 1st, 3rd, 5th, 10th, 24th, 48th and 72nd h. HPT was higher in CNTR group until 72th h and MET group at 48th, 72nd and 96th h. TBARs concentrations were statistically higher in MET and LID groups at 0 hour, in ERT and MET groups at the 1st h, in MET group at the 3rd h, in MET and LID groups at the 5th and 10th h, in MET group at the 48th, 72nd and 96th h (P < 0.05). MPO concentrations was higher in LID group at the 3rd, 5th, 10th and 96th h, and in ERT group at the 72nd h (P < 0.05). TGF-β concentrations were particularly high in MET group at the 3rd, 5th, 48th and 72nd h, and in LID group at the 10th, 24th, and 96th h (P < 0.05). Discussion: APPs (HPT, SAA, FIB), which are important regulators of inflammation in cows and sheep, were higher generally in MET and LID groups and inflammation persists in these two groups and, therefore, metoclopramide and lidocaine are less effective in early postoperative POI treatment. Because, significant increase in serum TBARs and MPO concentrations was considered as an important indicator of oxidative stress and inflammatory response MPO concentrations was particularly high until 10th h in LID group, and TBARs concentrations was high both MET and LID groups throughout the study, this was correlated with higher neutrophil infiltration in the postoperative early period than the other groups. It is known that TGF-β, an inflammatory cytokine, is correlated with various smooth muscle disorders in humans. In this study, TGF-β concentration were higher in the MET and LID groups. High concentration of this cytokine might have led to decrease contractions in smooth muscles, thereby slowing down the intestinal transition. In conclusion, based on the presence of pro-inflammatory markers in this study, erythromycin seems to be the most suitable prokinetic drug in lambs. Moreover, lidocaine and metoclopramide are not as successful in small ruminants as reported in other species.